Regulatory Algorythms as a Constructive Element of the Psyche Homo Sapiens and Agi: Part 2 - Kruglov, A. G; Kruglov, A. A. (Transactions on Engineering and Computing Sciences, 2025)
The structural unit of the unified homeostatic continuum (HC) of biological organisms is a heteronomous metamere in the form of an updated regulatory algorithm (RA). The stimulus for RA updating is violation of the HC information symmetry. Information fields of extra/interoception are of an external nature to the psyche. The psyche’s main function is to recognize, objectify, and eliminate significant information asymmetries in the reflected continuum of the external environment. The deterministic reaction of the psyche to disturbances in the HC is the updating of the interaction interface in the psyche/external environment system, consciousness. Interface updating stages are described in the text. In the mental RA of the socio-cultural genesis of Homo Sapiens, as frustration constructs become more complex, the accuracy and clarity of the constructive parameters of the goal image, the final phase of RA completion, decreases/loses. The result is epigenetically-developed psychological constructs of socio-cultural genesis, one of which is the need for permanent scanning of the external environment through the exertion of arbitriraly attention (consciousness) with insufficiently clear parameters of the goal image, the completion phase of the RA. The mechanisms of development of "intuitive psychology" and understanding of cause-and-effect relationships are given. Constructive (non-hierarchical) differences between vital and mental homeostatic needs are considered. Some principles of the structure of the psyche are presented, which it is advisable to consider when constructing AGI architectonics.